2002
DOI: 10.1002/pd.464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the risk of tuberous sclerosis in cases with prenatal diagnosis of cardiac rhabdomyoma

Abstract: The present data suggest that 39% of in utero suspected cardiac rhabdomyoma would have tuberous sclerosis. Family history and multifocality remain the strongest predictors of tuberous sclerosis, whereas size of the cardiac tumor can not reliably be used to predict tuberous sclerosis in prenatal counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…In symptomatic patients, surgery is sometimes attempted in order to debulk the tumor and is associated with high morbidity and mortality . Medical treatment was limited to supportive therapy until recent case reports described optimal outcomes in children with cardiac rhabdomyomas treated with mTOR inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…In symptomatic patients, surgery is sometimes attempted in order to debulk the tumor and is associated with high morbidity and mortality . Medical treatment was limited to supportive therapy until recent case reports described optimal outcomes in children with cardiac rhabdomyomas treated with mTOR inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gamzu et al 19 reported their study evaluating the risk of tuberous sclerosis in cases with prenatal diagnosis of cardiac rhabdomyoma and found that 39% of cases with suspected cardiac rhabdomyomas in-utero would have tuberous sclerosis. Family history and multifocality remain the strongest predictors of tuberous sclerosis, and the cardiac tumor cannot be used reliably to predict tuberous sclerosis in prenatal counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gamzu et al . reported that multifocality of the tumor diagnosed in utero was the strongest evidence of tuberous sclerosis, 18 but the tumor in this case is solitary.…”
Section: Discussionmentioning
confidence: 51%